MANAJEMEN BLENDED LEARNING BERBASIS WHATSAPP PADA MASA PANDEMI COVID-19 (Studi Kasus di SMAN 1 Manggelewa) - Muh. Elyas Prabowo; Muslimin Muslimin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
Indonesian education is improving itself according to all the limitations that occurred during the Covid-19 Pandemic. Blended Learning is one of the solutions for implementing learning in the midst of a pandemic. SMAN 1 Manggelewa is one of the schools that applies Blended Learning in learning during a pandemic. This study aims to determine the policy of the West Nusa Tenggara Provincial Government on high school level learning, know the WhatsApp-based Blended Learning management model at SMAN 1 Manggelewa, know the advantages and disadvantages of the WhatsApp-based Blended Learning model at SMAN 1 Manggelewa and find out how the Blended Learning model is effective for high school level in the future. The research used a descriptive qualitative approach. Primary data were obtained from SMAN 1 Manggelewa, while secondary data were obtained from the appropriate literature. The results showed that the West Nusa Tenggara Provincial Government continued the central government regulation, namely limiting face-to-face learning. SMAN 1 Manggelewa has implemented WhatsApp-based Blended Learning through groups managed by subject teachers. The implementation of Blended Learning at SMAN 1 Manggelewa went well despite several obstacles. For future projections, Blebded Learning can be further collaborated with technology in the form of an LMS (Learning Management System) through Moodle.